Evaluasi Pengawasan Pengadaan Barang dan Jasa pada Pemerintah Kota Gorontalo: Studi Kasus Inspektorat Kota Gorontalo - Siti Nur Anisa Ali; Rio Monoarfa; Yustina Hiola, (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to identify and evaluate the form of the goods and services procurement oversight in the Gorontalo City Government conducted by the Gorontalo City Inspectorate. This study uses a qualitative method with a case study approach. The data collection techniques include observation, interviews, and documentation. The data analysis techniques involve data reduction, data display, and conclusion drawing/verification. The results of study indicate that the task planning in the oversight process of goods and services procurement by the Gorontalo City Inspectorate can proceed through several stages as follows: task preparation, task risk assessment, preliminary survey, work program, and the requirement for a Management Representation Letter (MRL). The task implementation in the oversight process of goods and services procurement by the Gorontalo City Inspectorate can proceed through several stages mentioned as follows: preliminary discussions, data and information collection, analysis and evaluation of evidence, a list of obtained evidence, task documentation, and task supervision. In communicating the task results in the goods and services procurement oversight process by the Gorontalo City Inspectorate, several stages need to proceed: task result discussion, task result reporting, and follow-up monitoring.